Serum sclerostin and cytokine responses to prolonged sculling exercise in highly-trained male rowers - Jürimäe, J.; Purge, P.; Tillmann, V. (Journal of Sports Sciences, 2021)
This study examined sclerostin and cytokine responses to an endurance training session in male single sculling rowers. Sixteen highly trained rowers performed a 2-h rowing exercise (distance: 23.8 ± 0.9 km; heart rate: 138 ± 8 beats.min-1; intensity: 79.8 ± 2.1% of the anaerobic threshold). Rowing resulted significant increment (p < 0.05) in sclerostin (36%), interleukin (IL)-6 (345%), IL-10 (129%) and monocyte chemoattractant protein-1 (MCP-1) (132%), while increases in irisin (6%) and tumour necrosis factor-a (3%) were not significant (p > 0.05). There was a correlation between the pre-to-post-exercise increase in sclerostin and the distance covered (r = 0.67; p = 0.005) as a marker of energy expenditure, and weekly training volume (r = 0.66; p = 0.005) as a marker of training stress. Post-exercise gain in MCP-1 was the most important predictor of post-exercise gain in sclerostin (ß = 0.543; p = 0.040). In conclusion, acute non-impact rowing training session with a total body mode induced increases in sclerostin and also in IL-6, IL-10 and MCP-1 concentrations, while post-exercise gain in MCP-1 was the main determinant of post-exercise gain in sclerostin. Exercise-induced increase in sclerostin could be regarded as a signal for metabolic reaction to the energy cost of acute exercise in rowers.